Retrospective study of the recurrence risk of preterm birth in Japan. (1st February 2022) - Seyama, Rie; Makino, Shintaro; Nojiri, Shuko; Takeda, Jun; Suzuki, Toshifumi; Maruyama, Yojiro; Takeda, Satoru; Itakura, Atsuo
Abstract: Background: A history of preterm birth is a risk factor for preterm birth in a future pregnancy, and there are some reports of prevention methods, such as the administration of progesterone. However, the rate of recurrence of preterm birth in Japan has not been clarified, and there is no data for judging whether these preventive methods are effective. Objective: To clarify the risk of recurrence of preterm birth and preterm prelabor rupture of membranes (pPROM) in Japan. Materials and methods: A retrospective study was conducted using the perinatal registration database of the Japan Obstetrics and Gynecology Society for the Perinatal Center from 2014 to 2016. There were 704, 418 subjects, of which 190, 990 were excluded those with unknown maternal information, those under the age of 20 years, those with perinatal disease related to preterm birth, and first-time mothers. Results: Logistic model unavailable and multivariate analysis were performed. An analysis of the preterm birth history indicated the risk of preterm birth in the current pregnancy, and the odds ratio for preterm birth recurrence once, twice, and three times or more was 3.3, 6.6, and 7.8, respectively. As a secondary analysis, we analyzed whether the history of pPROM is a risk factor of recurrence of pPROM and found a significant association with an odds ratio of 3.4. Conclusion: Having a preterm birth history increases the risk of recurrence of preterm birth, and the risk of recurrent preterm birth increases as the number of preterm births increases. Although this report is intended for high-risk pregnancies wherein the rate of preterm birth is high, as previously reported, our data indicate that in Japan, preterm birth is a risk factor of recurrent preterm birth.